2013
DOI: 10.1063/1.4815848
|View full text |Cite
|
Sign up to set email alerts
|

A study of tungsten spectra using large helical device and compact electron beam ion trap in NIFS

Abstract: Tungsten spectra have been observed from Large Helical Device (LHD) and Compact electron Beam Ion Trap (CoBIT) in wavelength ranges of visible to EUV. The EUV spectra with unresolved transition array (UTA), e.g., 6g-4f, 5g-4f, 5f-4d and 5p-4d transitions for W +24-+33 , measured from LHD plasmas are compared with those measured from CoBIT with monoenergetic electron beam (d2keV). The tungsten spectra from LHD are well analyzed based on the knowledge from CoBIT tungsten spectra. The C-R model code has been deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…Although the electron density in EBITs is lower than tokamak fusion * jon.grumer@teorfys.lu.se plasma densities, by around 2 orders of magnitude, M1 lines have been observed in fusion devices, e.g., as mentioned above the 2s 2 2p 3 2 D 5/2 -2 D 3/2 M1 decay in Fe XX [3]. Also, at the National Institute for Fusion Science in Japan, Morita et al [7] reported the observation of M1 transitions in the visible region for highly charged tungsten ions. Previously spectra from tokamaks made a great impact on the study of M1 and other forbidden transitions (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Although the electron density in EBITs is lower than tokamak fusion * jon.grumer@teorfys.lu.se plasma densities, by around 2 orders of magnitude, M1 lines have been observed in fusion devices, e.g., as mentioned above the 2s 2 2p 3 2 D 5/2 -2 D 3/2 M1 decay in Fe XX [3]. Also, at the National Institute for Fusion Science in Japan, Morita et al [7] reported the observation of M1 transitions in the visible region for highly charged tungsten ions. Previously spectra from tokamaks made a great impact on the study of M1 and other forbidden transitions (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…UTAs consisting of W 24+ -W 33+ and W 27+ -W 42+ also appeared at 19-33 Å and 46-53 Å, respectively. The identification of charge states of the UTA was performed by comparing the spectra obtained in LHD and the compact electron beam ion trap (CoBIT) with CR model calculations [11,[37][38][39]. It is worth noting that the UTAs at around 50 Å have been used to evaluate tungsten ion concentrations in tokamak experiments [40].…”
Section: Tungsten Line Emissions In the Visible Vuv And Euv Wavelength Rangesmentioning
confidence: 99%
“…Spectroscopic studies for emission from W ions in combination with a tungsten pellet injection technique have been intensively conducted on the Large Helical Device (LHD) for contribution to tungsten transport studies in tungsten divertor fusion devices represented by ITER and for expansion of the experimental database of tungsten line emissions [11][12][13][14]. The electron temperature, T e , of the LHD core plasmas with a tungsten pellet injection ranges from 0.5 keV to 3.5 keV, which is close to that of the edge plasmas in ITER around the last closed flux surface, including the scrape-off layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity is also a hindrance to the necessary diagnostics of this contaminationvery little is known about the structure of the different ions of Tungsten. A major effort in later years on the spectroscopy of Tungsten, has been to understand these complex systems and be able to help in developing a new energy source [32,33,34].…”
Section: Complementing Experimentsmentioning
confidence: 99%